Influence of Near-Fault Ground Motions with Fling-Step and Forward-Directivity Characteristics on Seismic Response of Base-Isolated Buildings. Issue 3 (23rd February 2021) - Bhagat, Satish; Wijeyewickrema, Anil C.; Subedi, Naresh
ABSTRACT: The behavior of base-isolated buildings under near-fault (NF) ground motions with fling-step and forward-directivity characteristics is investigated using three-dimensional nonlinear finite element models. Nonlinear response history analysis (NLRHA) is also carried out after removing the dominant pulse from the NF ground motion records. The results obtained for 10-story base-isolated buildings with and without shear walls, indicate that NF ground motions with fling-step and forward-directivity characteristics produce large inter-story drift ratios and floor accelerations, compared to the case when the dominant pulse is removed. Additional NLRHA carried out using artificial pulses shows that the isolator and superstructure responses are larger for pulses with fling-step characteristics, compared to pulses with forward-directivity characteristics.